Butenolide Insecticide Flupyradifurone Affects Honey Bee Worker Antiviral Immunity and Survival - Harwood, Gyan P.; Prayugo, Vincent; Dolezal, Adam G. (Frontiers in Insect Science, 2022)
Honey bees face many environmental stressors, including exposure to pesticides and pathogens. A novel butenolide pesticide, flupyradifurone, was recently introduced to the US and shown to have a bee-friendly toxicity profile. Like the much-scrutinized neonicotinoids that preceded it, flupyradifurone targets the insect nervous system. Some neonicotinoids have been shown to interfere with antiviral immunity, which raised the concern that similar effects may be observed with flupyradifurone. In this study, we investigated how flupyradifurone and a neonicotinoid, clothianidin, affect the ability of honey bee workers to combat an infection of Israeli acute paralysis virus (IAPV). We exposed workers to field-realistic doses of the pesticides either with or without co-exposure with the virus, and then tracked survival and changes in viral titers. We repeated the experiment in the spring and fall to look for any seasonal effects. We found that flupyradifurone caused elevated mortality in the fall, but it did not lead to increased virus-induced mortality. Flupyradifurone also appeared to affect virus clearance, as bees co-exposed to the pesticide and virus tended to have higher viral titers after 48 hours than those exposed to the virus alone. Clothianidin had no effect on viral titers, and it actually appeared to increase resistance to viral infection in spring bees.